Economic Performance of Commercial Poultry Farms in Oyo State Nigeria - Bamiro, Olasunkanmi M. (International Journal of Poultry Science, 2008)
This study focuses on the economic performance of the commercial poultry farms in some selected Local Government areas of Oyo State, Nigeria. Data was collected from 71 farmers using purposive sampling technique. The result of the study shows that the profitability of poultry enterprise is a function of enterprise combination as well as scale of production. The budgetary analysis shows that in all enterprise combinations, farmers that operate on large scale have highest gross margins. On the basis of enterprise combinations, the egg production enterprise records the highest gross margin while the broiler production enterprise records the lowest gross margin. The regression analysis shows that flock size, feed, labour have significant positive effects on the value of output while interaction between layers and broilers have negative impact on the value of output. In the allocation of all the variable inputs the poultry farmers are not efficient.